Barriers to public participation in developmental projects : a Nigerian community perspective (case study of the Gbaran-Ubie oil and gas project) - Akoh, Emmanuel Inalegwu (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
This research paper is broken up into three sections, namely an evaluation report, a literature review and research methodology. The evaluation report section is the assessment of the current state of change readiness within the Eskom Contact Centre's based upon what the literature on change readiness prescribes. The timing of the change readiness assessment is just prior to significant organisational change. The organisational change that was about to be initiated by the organisation was initiated from the boardroom of the most senior echelons of the organisation, and was directed in a top down approach, being a strategic organisational change. The change is deemed to be critical to the organisation being able to meet its long term strategic and sustainability objectives. A critical examination of the literature explored the meaning of change readiness, the importance of it and explained the consequences for organisations that commit to transformational agendas without being ready. Key concepts such as such resistance to change and organisational inertia are described and differentiated from change readiness. The ADKAR change model and its change readiness assessment instrument were used due to the organisations preference for the model. The ADKAR model formed the framework for the analyses of the data, the discussion of the results and the recommendations to the organisation. The research conducted was quantitative in nature; a questionnaire was distributed to the employees of the seven Eskom Contact centre sites around the country through an email. A slightly modified version of the ADKAR change readiness questionnaire was sent via email with an on-line questionnaire link on it; and questions on individual readiness for change were used to assess the level of readiness of the employees. Most of the descriptive and inferential statistics were analysed with the use of Excel (version, 2010), with Factor Analysis being done in Statistica. The results of the research showed that: [iii] - The factors as proposed by the ADKAR change readiness assessment questionnaire (i.e. Awareness, Desire, Knowledge, Ability and Reinforcement) are not different enough to be considered as independent factors for this data set. Based on factor analysis, the factors were subsequently amended from five to three, namely Readiness, Opportunity Realisation and Uncertainty. - The Contact Centre employees were somewhat ready for change. - The Contact Centres needed to focus on all amended ADKAR factors in order to improve the readiness of the department. - The readiness levels in response to the roll out were more or less uniform. The study shows that given Eskom's preference for the ADKAR model, future research within Eskom should therefore be conducted more circumspectly with respect to ascertaining the validity of the ADKAR factors. The study also makes mention that future work and/or research will need to be conducted, specifically on the readiness of the organisation itself, in order to improve the probability of transformational success. The ADKAR assessment is a people focused assessment and therefore focuses only on the readiness of the individual. Factors such as the adequacy of the current state of resources within the organisation, which incorporate aspects such as infrastructure, technology and staffing, will also need to be assessed to make a more holistic statement of change readiness. A concise review of the literature is incorporated into the Evaluation Report of Section 1 to underpin the study. In Section 2 a more extensive review of the literature is presented. Similarly, the design of the research is discussed in more detail in Section 3 to both describe and justify the appropriateness of the research methodology, and to give a detailed account of the way in which the research was carried out.
Keywords: Gbaran-Ubie oil and gas project -- Public opinion; Community development -- Nigeria; Economic development -- Nigeria -- Environmental aspects